ERİŞKİN BAŞLANGIÇLI TİNU SENDROMU: BİR OLGU SUNUMU - MURAT, Berna; ÖZDEMİR, Ali (Cerrahpaşa Medical Journal, 2014)
Background.- A Turkish woman aged 30 years who presented with a 2-month history of uveitis was admitted duo to acute renal failure. She has had significant fall in creatinine clearance, rise in BUN and creatinine levels, findings consistent with tubular dysfunction. In addition, there was anergy to PPD test, high levels of serum IgG and anticardiolipin antibodies, low level of serum C3 complement. With percutaneous renal biopsy; diffuse mononuclear cellular infiltration, uniform tubular atrophy, few intratubular hyaline casts, slight focal interstitial edema and fibrosis was detected. Neither vascular nor glomerular changes were seen. There was no deposition of immune globulin, fibrinogen or complement components with immünofluorescence staining. Although serum BUN and creatinine levels declined dramatically at the beginning with supportive treatment, they persisted at supranormal levels during follow-up (BUN: 20 mg/dl and creatinine: 1.9 mg/dl). Therefore, after a follow-up of one month, oral prednisone therapy was began which led to further decreases in BUN and creatinine levels. This observation points out that steroid treatment may be useful in the treatment of TINU syndrome.